Risks for animal health related to the presence of fumonisins, their modified forms and hidden forms in feed. (25th May 2018) - ,; Knutsen, Helle‐Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; et al.
Abstract: Fumonisins, mycotoxins primarily produced by Fusarium verticillioides and Fusarium proliferatum, occur predominantly in cereal grains, especially in maize. The European Commission asked EFSA for a scientific opinion on the risk to animal health related to fumonisins and their modified and hidden forms in feed. Fumonisin B1 (FB1 ), FB2 and FB3 are the most common forms of fumonisins in feedstuffs and thus were included in the assessment. FB1, FB2 and FB3 have the same mode of action and were considered as having similar toxicological profile and potencies. For fumonisins, the EFSA Panel on Contaminants in the Food Chain (CONTAM) identified no‐observed‐adverse‐effect levels (NOAELs) for cattle, pig, poultry (chicken, ducks and turkeys), horse, and lowest‐observed‐adverse‐effect levels (LOAELs) for fish (extrapolated from carp) and rabbits. No reference points could be identified for sheep, goats, dogs, cats and mink. The dietary exposure was estimated on 18, 140 feed samples on FB1–3 representing most of the feed commodities with potential presence of fumonisins. Samples were collected between 2003 and 2016 from 19 different European countries, but most of them from four Member States. To take into account the possible occurrence of hidden forms, an additional factor of 1.6, derived from the literature, was applied to the occurrence data. Modified forms of fumonisins, for which no data were identified concerning both the occurrence and the toxicity, were not included in the assessment. Based on mean exposure estimates, the risk of adverse health effects of feeds containing FB1–3 was considered very low for ruminants, low for poultry, horse, rabbits, fish and of potential concern for pigs. The same conclusions apply to the sum of FB1–3 and their hidden forms, except for pigs for which the risk of adverse health effect was considered of concern.